A STUDY ON THE PATHOLOGICAL AND DIAGNOSIS OF EIMERIA SPECIES INFECTION IN JAPANESE QUAIL - N.H. Mohammad (Basrah Journal of Veterinary Research)
This study was conducted to detect the intestinal coccidial types in87Japanese quails (coturnix coturnix japonica)the birds were purchased from different parts of Nenevah governorate. The current study reveals that the total percentage of infection with Eimeria spp.oocysts 49.4%. Three species were diagnosed,according to their percentage they are:E.tsunodai 44.8%,E. uzura 34.5%,E. bateri 24.1%. The higher rates were in young birds. There was no significant difference with respect to sex. The results showed the higher infection rate and intensity was recorded in caecum infection with three species of Eimeria was most frequent in Japanese quails with percentage 46.5%. Macroscopical lesions of infected birds revealed thatsoftening of feces,thickening of mucosa and hemorrhagein caecum. Microscopically lesions characterized by sever hyperplasia of epithelial cell with construction of intestinal gland cavities in small intestine, caecum and presence of odema between muscle fibers with different development epithelial cells and infiltration with inflammatory cells. This study is regarded the first study in detection of species and pathological effect of Eimeriain Japanese quails in Nenevah governorate.